APOE and CETP TaqIB polymorphisms influence metabolic responses to 'Hibiscus sabdariffa' L. and 'Gynostemma pentaphyllum' Makino tea consumption in hypercholesterolemic subjects - Jeenduang, Nutjaree; Sangkaew, Boonnisa; Chantaracha, Pacharee; Chanchareonsri, Sirada; Plyduang, Thunyaluk; Thitdee, Wanida; Samae, Cathaleeya; Pitumanon, Wacharaporn (Asia Pacific journal of clinical nutrition, 2017)
Background and Objectives: Hibiscus sabdariffa L. (HS) and Gynostemma pentaphyllum Makino (GP) have been used as traditional medicines to treat diabetes and hypercholesterolemia. Nevertheless, there is interindividual variation in the metabolic responses to HS and GP consumption. This may be due to genetic factors. The aim of this study was to investigate the effects of HS and GP tea consumption on anthropometric data, fasting blood glucose (FBG), and lipid concentrations in hypercholesterolemia subjects with different genotypes of the APOE and CETP TaqIB polymorphisms. Methods and Study Design: Forty-eight subjects with hypercholesterolemia were given either HS or GP tea for 30 days. Anthropometric and biochemical variables were determined, and APOE and CETP TaqIB polymorphisms were analyzed using the polymerase chain reaction- restriction fragment length polymorphism (PCR-RFLP). Results: E4 (p=0.008) and homozygous B1B1 (p=0.010) carriers had significantly decreased HDL-C concentrations after HS consumption; in addition, B2 carriers who consumed HS showed significantly decreased triglyceride (TG) concentrations (p=0.039). Regarding GP consumption, non-E4 carriers had significantly decreased HDL-C (p=0.009) and FBG (p=0.042) concentrations. Furthermore, B2 carriers had significantly decreased total cholesterol (TC) (p=0.045), HDL-C (p=0.004), and FBG (p=0.026) concentrations. Conclusions: HS consumption may have beneficial effects with respect to TG concentrations in the B2 carriers, but it may adversely affect HDL-C concentrations in homozygous B1B1 and E4 carriers. In contrast, GP consumption may have favorable effects on TC and FBG concentrations but not on HDL-C concentrations for B2 and/or non-E4 carriers.